ANALISIS PERILAKU DEPOSAN PERBANKAN DI INDONESIA (STUDI KASUS BANK SYARIAH DAN KONVENSIONAL) - Mustabsyirah Musri; Ali Rama (Faculty of Economics and Business, 2015)
This study attempts to empirically analyze the factors that are important in determining the Islamic bank deposit and conventional bank deposit in the case of Indonesia. By employing the vector autogression analysis along with the associated granger causality, variance decomposition and impulse response function for all banks in Indonesia, the study examine the importance of selected financial and macroeconomic variables in determining the level of deposit of Islamic banks as well as conventional banks. Using monthly data, the study covers the period from January, 2004 to September, 2013. The results highlight the influential role of interest rate and rate of return in determining the level of bank deposit (Islamic and conventional). The finding also shows the existence of interest risk on the Islamic bank system. Another finding reveals that inflation, stocks price and economic growth influence the level of deposit in the banking system.